Penguatan Pengetahuan dan Akses Masyarakat terhadap Layanan Keluarga Berencana - Tria Jessica Tissa Nino; Emanuel Kosat (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service activity aims to improve knowledge and access to family planning services in Lamabelawa Village, Witihama District, East Adonara. The main target of this activity is the Fertile Age Couple (PUS). The socialization activities covered the importance of family planning and reproductive health. The material presented included the definition of family planning, types of contraceptives, the benefits of family planning, and the importance of maintaining reproductive health. The approach used in this activity is the lecture method and interactive discussion. With this method, participants not only receive information, but also have the opportunity to actively participate, ask questions, and share their experiences related to family planning. The material in this activity was delivered by the Witihama Sub-district Family Planning Extension Agency who has competence in this field. Through this activity, it is expected that PUS in Lamabelawa Village can understand and apply the knowledge gained about family planning in their daily lives. In addition, this activity also aims to increase community awareness of the importance of reproductive health, so as to reduce the unplanned birth rate and improve family welfare. The results of this activity showed high enthusiasm from the participants as well as an increase in their understanding of the importance of family planning programs and reproductive health.